KRITIK ULAMA TERHADAP TAFSIR SUFI DAN UPAYA REKONSTRUKSI BATAS-BATAS PENAFSIRANNYA - Muhammad Amzad; Rasyid Hidayatullah; Muhammad Iqbal Jamalul Lael; Akhmad Dasuki (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to reconstruct a systematic and operational framework of dhawabith al-tafsir al-isyari (methodological boundaries of Sufi interpretation) by synthesizing scholarly debates surrounding the legitimacy of Sufi Qur'anic exegesis. The research employs a qualitative approach through library research, utilizing primary sources comprising classical Ulumul Qur'an texts, namely Al-Itqan fi 'Ulum al-Qur'an by al-Suyuti, Mabahis fi 'Ulum al-Qur'an by Manna' al-Qattan, and Manahil al-'Irfan fi 'Ulum al-Qur'an by al-Zarqani, supplemented by relevant secondary sources from contemporary academic journals. Data were analyzed using descriptive-analytical methods through comparative examination of scholarly views across different periods. The findings reveal that Sufi exegesis (tafsir isyari) developed in two main variants (nazari (speculative) and isyari (moderate)) and has been subject to a long-standing scholarly debate that is fundamentally methodological rather than substantive in nature. Both rejecting and accepting scholars share three common grounds: the primacy of the literal (zahir) meaning, the rejection of Bathiniyah interpretation, and the importance of the exegete's personal qualification. Building on this convergence, this study reconstructs six operational dhawabith: non-negation of the literal meaning, support from valid scriptural evidence, non-contradiction with Islamic law and reason, prohibition of exclusivist claims over inner meanings, semantic-thematic coherence with the Qur'anic text, and the exegete's scholarly and spiritual integrity. The novelty of this research lies in its shift from descriptive-polemical discourse to a normative-constructive evaluative framework, providing Islamic higher education institutions with a practical instrument for critically and proportionally assessing Sufi exegetical works.